2022
DOI: 10.1128/spectrum.02013-21
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Antimicrobial Peptide Derived from Bony Fish IFN1 Exerts Potent Antimicrobial and Anti-Inflammatory Activity in Mammals

Abstract: Type I interferons play crucial role in antiviral immunity in both vertebrates and invertebrates. The powerful antimicrobial activity is recently reported in nonmammalian vertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 56 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…17 Recently, the peptide type I interferon (IFN-1) from the grass carp has been discovered as a strong antimicrobial and anti-inflammatory agent. 18 In particular, authors identified a portion derived from the fifth helical region, rich in basic amino acids and highly cationic, with potent antibacterial effect both against Gram-positive and Gram-negative bacteria by disrupting and permeating membrane, respectively. The minimum bactericidal concentration (MBC 90 ) ranges from 8 to 16 μg/mL for Gram-negative and from 2 to 4 μg/mL for Gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Recently, the peptide type I interferon (IFN-1) from the grass carp has been discovered as a strong antimicrobial and anti-inflammatory agent. 18 In particular, authors identified a portion derived from the fifth helical region, rich in basic amino acids and highly cationic, with potent antibacterial effect both against Gram-positive and Gram-negative bacteria by disrupting and permeating membrane, respectively. The minimum bactericidal concentration (MBC 90 ) ranges from 8 to 16 μg/mL for Gram-negative and from 2 to 4 μg/mL for Gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The minimum bactericidal concentration (MBC 90 ) ranges from 8 to 16 μg/mL for Gram-negative and from 2 to 4 μg/mL for Gram-positive bacteria. 18 Conversely, the antiviral activity of fish peptides has been poorly elucidated, and mainly, they interfere with fish virus infections. In detail, β-defensins 1 19 and the hepcidin 1-5 were demonstrated to block the viral hemorrhagic septicemia virus (VHSV) and nervous necrosis virus (NNV) infection, by inhibiting viral particles adsorption and penetration into host cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioavailability of AMPs is greatly reduced by biological digestion, which diminishes their effectiveness (10). Recently, carboxylmethyl chitosan (CMCS) have been applied as the polymer materials to inhibit the degradation of bioactive peptide (16,17). In our previous study, we identified a AMP gcIFN-20H (I20) with high efficiency and broad-spectrum bactericidal ability from grass carp type I interferon (IFN1) (18).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, carboxylmethyl chitosan (CMCS) have been applied as the polymer materials to inhibit the degradation of bioactive peptide ( 16 , 17 ). In our previous study, we identified a AMP gcIFN-20H (I20) with high efficiency and broad-spectrum bactericidal ability from grass carp type I interferon (IFN1) ( 18 ). We conjugated gcIFN-20H and CMCS to develop a novel AMP reagent CMCS-gcIFN-20H (CMCS-20H), and found CMCS-20H can retard degradation, prevent bacterial infection, improve intestinal mucosal barrier and regulate intestinal flora ( 19 ).…”
Section: Introductionmentioning
confidence: 99%